1993
DOI: 10.1002/mrm.1910290410
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced first pass myocardial perfusion imaging: Correlation between myocardial blood flow in dogs at rest and during hyperemia

Abstract: The sensitivity of contrast-enhanced MR first pass perfusion imaging in detection and quantification of hypoperfused myocardium was evaluated using an instrumented, closed-chest dog model where graded regional hypoperfusion was induced by applying predetermined levels of stenosis to the left anterior descending artery (LAD). All measurements were performed at rest and under stress induced by dipyridamole (DIP). Myocardial perfusion was assessed both with MR and radiolabeled microspheres injected immediately be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
195
0
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(202 citation statements)
references
References 26 publications
5
195
0
2
Order By: Relevance
“…Reduced signal intensity on first-pass MRI contrast images has been shown to be associated with reduced blood flow, 4 although this relationship may not be linear when higher doses of extravascular gadolinium-based MRI contrast agents are used. 13 In infarct regions, however, microvascular myocardial blood flow may not return to normal even after epicardial revascularization, 14 the so-called no-reflow phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced signal intensity on first-pass MRI contrast images has been shown to be associated with reduced blood flow, 4 although this relationship may not be linear when higher doses of extravascular gadolinium-based MRI contrast agents are used. 13 In infarct regions, however, microvascular myocardial blood flow may not return to normal even after epicardial revascularization, 14 the so-called no-reflow phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…A number of interrelated factors, including reduced regional blood flow, 4,5,15 increased capillary permeability, 16 and increased interstitial volume, 17 may produce HYPER within viable but previously ischemic myocardium. In the present study, HYPER differed in both contrast enhancement pattern and late myocardial function compared with HYPO, COMB, or REMOTE.…”
Section: Discussionmentioning
confidence: 99%
“…6 -12 Parameters for the assessment of myocardial perfusion are usually gained by analyzing the first pass of a contrast agent bolus through the myocardium. 6,9,13,14 With extensive modeling, quantitative determination of myocardial perfusion is possible; however, this approach relies on several assumptions that may not be fulfilled in patients. 13,[15][16][17] We have recently shown that a linear fit of the upslope is easy to perform, is highly reproducible, and shows promising accuracy in a selected patient population.…”
mentioning
confidence: 99%
“…One possible approach to assess perfusion with MRI is contrast-enhanced first pass perfusion imaging (7). The basic principle is the tracking of the signal intensity change after the i.v.…”
mentioning
confidence: 99%